Die identifisering van boustene vir die ontwerp van ? etiek vir ontmoeting (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2012)
This study presents a framework for an ethics of engagement. The basis for this study is the question how one should engage with unknown people? The study is a literature study that analyses important concepts in an ethics of engagement such as mercy, care, service and community. An investigation into the Biblical parable of the “merciful Samaritan” and the business case study, “The parable of the Sadhu”, provides useful pointers in the analysis, design and development of elements that can be used when an ethics of engagement will be formulated. This study is also informed by a search for an earthly spirituality (based on research done by E. Conradie). An earthly spirituality suggests that life and community with people should be experienced in the precence of God. This study also employs perspectives from literature and film. These perspectives supported the observation that there are several sides to life and that enagement with the “other” takes place in the different sides of life. It was also noteable that engagement does not only imply to meet other people but also oneself. The study suggests that an ethics of engagement should be understood as the expressing of one’s attitude/ intension/ conviction/ disposition of neighbourly love through responsible acts towards other people in order to create an earthly spirituality.